Meta-analysis and systematic review: The administration of glucocorticoids, as a line of treatment for COVID-19 patients, could result in lowering mortality - Zhou Enhao; Li You; Hu Danlan; Dai Yuchi; Wang Tian; Yang Chun (Taylor & Francis Group, 2022)
The aim of this meta-analysis was to investigate the association between the use of glucocorticoids and the mortality of covid-19 patients. Trials were identified through a comprehensive systematic search of four medical databases including PubMed, Cochrane Library, Web of Science, and Embase. We also searched for relevant papers using the Google search engine and major Preprint platforms including Medrix, bioRxiv, and SSRN. A meta-analysis was performed on the pooled results of these studies. Fourteen studies were enrolled. Five studies were Chinese, and nine were foreign. In the foreign studies, we found use of steroids was associated with a decrease in mortality (RR, 0.81; 95% CI 0.68-0.97; p = 0.02) whilst in the Chinese studies the use of steroids was associated with an increase in mortality (RR, 1.70; 95% CI 1.10-2.63; p = 0.02). The foreign studies included high-dose and medium-dose groups. The medium-dose glucocorticoid group (0.5 mg/kg/d ≤ Prednisone ≤ 1.0 mg/kg/d) showed an association with decreased mortality of covid-19 patients (RR 0.86; 95% CI 0.75-1.00; p = 0.05). We also found an association with decreasing mortality of covid-19 patients (RR 0.65; 95% CI 0.43-0.98; heterogeneity p = 0.04) in patients treated for ≤ five days. In summary, this meta-analysis demonstrated that the use of a medium dose of glucocorticoids for a short time is likely to decrease mortality, although this needs clinical confirmation.